Vitamin D deficiency associated with hyperphosphatemia in children - Virú-Loza, Manuel André (2021)
Children with vitamin D deficiency can have normal or high phosphorus despite having a high parathyroid hormone test (PTH). Pseudohypoparathyroidism (PHP) is characterized by hyperphosphatemia. The similarity that can occur between vitamin D deficiency associated with hyperphosphatemia and PHP makes it important to review case reports of vitamin D deficiency associated with hyperphosphatemia to understand why this association may occur and what is the relevance of studying the vitamin D level in children with suspected PHP. The aim of this review was to identify reports of children with vitamin D deficiency associated with hyperphosphatemia and to discuss the mechanisms of this association. Reports of 7 children cases were identified. Vitamin D deficiency could reduce the phosphaturic response to elevated PTH. It is concluded that it is important to rule out vitamin D deficiency in all children with suspected PHP